"Preparing students for what lies ahead": Teaching dental public health leadership with simulated community partners. (2nd April 2019) - McCunney, Dennis; Davis, C. Ervin; White, B. Alex; Howard, John
Abstract : Purpose: Dental school curricula increasingly emphasize training in leadership, public health, community engagement and collaboration. Leadership may be defined as a relational process for inspiring and influencing positive change. Leadership training focused on effectively building relationships and partnerships to improve community health is particularly important with the increased emphasis on dental primary care, holistic care, rural care and health disparities. Dentists and other health care providers are encouraged to engage with communities and community partners and organizations to improve healthcare and overall health. To better educate and train dental students to meet these challenges, new and innovative methods of didactic and experiential coursework are needed. The paper aims to discuss these issues. Design/methodology/approach: The current study describes the development, delivery and preliminary evaluation of a community-engaged leadership training program for dental students. The program incorporated student-developed public health project proposals and sessions with simulated community partners based on a simulated rural community with specific oral and general health needs. Findings: Overall, students felt the training was realistic and valuable for developing leadership skills and preparing them for challenges that could not have been learned through didactic instruction alone. Students gained a better understanding of their own leadership styles, their strengths and weaknesses and their level of developed leadership competencies. Originality/value: This program is an innovative way to develop leadership applied to public health and community needs and should have implications for ways of teaching leadership to improve oral health outcomes.